Laparoscopic vs. Abdominal Radical Hysterectomy for Locally Advanced Cervical Cancer - Wang, Wenhui; Li, Lei; Wu, Ming; Ma, Shuiqing; Tan, Xianjie; Zhong, Sen (Frontiers in Oncology, 2019)
This study is to compare the survival outcomes of laparoscopic radical hysterectomy (LRH) to those of abdominal radical hysterectomy (ARH) for patients with LACC. Patients with FIGO 2009 stage IB2 to IIB LACC who underwent radical hysterectomy between 2001 and 2015 were identified. The disease-free survival (DFS) and overall survival (OS) were compared according to the surgical approach and were adjusted based on clinicopathologic characteristics. A total of 396 patients were included in the study, with 179 (45.2%) and 217 (54.8%) patients in the ARH and LRH groups, respectively. The LRH group showed a significantly lower amount of estimated blood loss, lower blood transfusion rate and shorter length of hospital stay. There were no significant differences in the 5-year DFS and 5-year OS between the LRH and ARH groups with the Kaplan-Meier method. However, multivariate analyses identified LRH as an independent prognostic factor for a poor DFS (hazard ratio [HR] 2.5; 95% confidence interval [95% CI] 0.19 to 0.87; p =0.02). The analysis of stage IB2 disease and the squamous subtype (61.9% and 87.9% of all participants, respectively) reached the same conclusion. Therefore, ARH was associated with a higher DFS than LRH in patients with LACC, especially in patients with stage IB2 disease or the squamous subtype.